Accuracy of the IDEXX SediVue Dx analyzer for quantifying RBC and WBC indices in the urine sediments of cats and dogs compared with manual microscopic evaluations - Blanco, Anthony E (Veterinary clinical pathology, 2022)
© 2022 American Society for Veterinary Clinical Pathology.